HUMANIZATION OF EDUCATION IN THE MODERN GLOBALYZATION CONDITIONS - Кадникова, Л. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The article examines the impact of contemporary globalization upon man and society’s spirituality and the need of humanitaryzation of the education system.